Peningkatan Hasil Belajar Siswa pada Pembelajaran Pendidikan Agama Katolik (PAK) Materi Aku Pribadi yang Unik melalui Metode Problem Based Learning (PBL) di Kelas III SDN 071163 Siwalubanua Tahun Pelajaran 2024/2025 - Yasabar Harefa (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This research aims to improve the learning outcomes of 3rd grade elementary school students in Catholic Religious Education subjects, especially the material "I am a Unique Personality", through the application of the Problem Based Learning (PBL) method. This Classroom Action Research (PTK) was carried out in two cycles with 5 students as research subjects. The research results showed an increase in the percentage of learning completion from 40% in the pre-cycle to 80% in the second cycle, as well as an increase in student learning activities from 60% to 100%. The application of PBL has proven to be effective in improving students' conceptual understanding, critical thinking abilities and problem solving skills in a small class context.